Composite substrate, flexible electrode and biosensor

By roughening the surface of the substrate body of the flexible electrode and grafting the functional groups to form a stable adhesive layer, the problem of adhesion failure between the substrate and the conductive layer is solved, and the life and reliability of the biosensor is improved.

CN119666945APending Publication Date: 2025-03-21SHANGHAI UNITED IMAGING MICROELECTRONICS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411632065.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The lifespan and reliability of the biosensor are reduced due to the failure of adhesion between the substrate and the conductive layer in biosensor.

Method used

By roughening the surface of the substrate body and grafting the functional groups, a stable adhesive layer is formed to enhance the bonding stability between the substrate and the conductive layer.

Benefits of technology

The bonding stability between the conductive layer and the substrate is improved, the life of the biosensor is extended, and the purity of the conductive layer is maintained, avoiding performance instability caused by the diffusion of the adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119666945A_ABST
    Figure CN119666945A_ABST
Patent Text Reader

Abstract

The invention provides a composite substrate, a flexible electrode and a biosensor, the composite substrate comprises a substrate body and a bonding layer, the surface of at least one side of the substrate body is provided with a rough structure, the surface of the substrate body with the rough structure carries functional groups, and the substrate body is grafted with the bonding layer through the functional groups. The surface of the base body is provided with the rough structure, so that the area of the graftable bonding material can be increased, and the density of the bonding material is improved. Meanwhile, the substrate body is grafted with the bonding layer through functional groups carried by the surface with the rough structure, and the bonding layer and the substrate background form chemical connection, so that the bonding force between the bonding layer and the substrate body is greater than the bonding force between the bonding layer and the conductive layer, and reasonable bonding force distribution is formed; and the bonding material in the bonding layer is prevented from expanding to the conductive layer, so that the bonding stability of the conductive layer and the substrate body is improved on the premise of not polluting the conductive layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of biosensors, and in particular to a composite substrate, a flexible electrode and a biosensor. Background Art

[0002] Flexible electrodes are widely used in biosensors. During their preparation process, multiple functional layers including substrate, conductive layer, insulating layer, sensing layer, etc. are often assembled in the form of stacking on each other. Flexible electrodes will be subjected to mechanical effects such as stretching, bending, and extrusion during use. Adhesion failure often occurs between layers, especially adhesion failure between the substrate and the conductive layer, which greatly affects the life and reliability of the biosensor. Summary of the invention

[0003] Based on this, it is necessary to provide a composite substrate, a flexible electrode and a biosensor to improve the adhesion effect between the substrate and the conductive layer and enhance the life and reliability of the biosensor.

[0004] The first aspect of the present application provides a composite substrate, comprising:

[0005] A substrate body, wherein at least one side of the surface of the substrate body has a rough structure, and the surface of the substrate body having the rough structure carries functional groups; and

[0006] The adhesive layer is grafted onto the substrate body through the functional group.

[0007] In some embodiments, the specific surface area of ​​the surface of the substrate body having the rough structure is 0.01 m 2 / g-1 m 2 / g; and / or

[0008] The roughness of the surface of the substrate body having the rough structure is 0.01 μm-1000 μm.

[0009] In some embodiments, the functional group includes one or more of a hydroxyl group, a carboxyl group, an amino group, an acrylic group, and an acrylic group derivative;

[0010] Optionally, the acrylic acid group derivative includes one or more of a methacrylic acid group, a cyanoacrylic acid group and an acryloyl chloride group.

[0011] In some embodiments, in a direction perpendicular to the surface where the rough structure is located, the depth of the rough structure is 0.01 μm-1000 μm.

[0012] In some embodiments, the material of the adhesive layer includes a viscous material with a molecular weight of 500Da-500000Da;

[0013] Optionally, the material of the adhesive layer includes one or more of polyacrylic acid, polyacrylate, cellulose, cellulose derivatives, polyvinyl alcohol, alginate, chitosan and collagen fibers;

[0014] Optionally, the cellulose derivative includes one or more of carboxymethyl cellulose and hydroxypropyl cellulose;

[0015] Optionally, the alginate includes one or more of sodium alginate, potassium alginate and ammonium alginate.

[0016] In some embodiments, the thickness of the adhesive layer is 0.1 μm-1 μm; and / or

[0017] In a direction perpendicular to the surface where the rough structure is located, the distance from the lowest point where the rough structure is grafted with the adhesive layer to the crest of the rough structure is 0.01 μm-200 μm.

[0018] In some embodiments, the material of the substrate body includes one or more of polyethylene terephthalate, polyimide, polyethylene naphthalate, polydimethylsiloxane, polyurethane and polycarbonate.

[0019] A second aspect of the present application provides a flexible electrode, comprising the composite substrate of the first aspect of the present application.

[0020] In some embodiments, the flexible electrode further includes a conductive layer, an insulating layer and a sensing layer, the composite substrate, the conductive layer, the insulating layer and the sensing layer are stacked in sequence, and the conductive layer is located on the side of the adhesive layer of the composite substrate.

[0021] A third aspect of the present application provides a biosensor, comprising the flexible electrode of the second aspect of the present application.

[0022] The above-mentioned composite substrate includes a substrate body and an adhesive layer. The surface of the substrate body has a rough structure, which can increase the area of ​​the grafted adhesive material and improve the density of the adhesive material, thereby improving the bonding stability between the conductive layer and the substrate body. At the same time, the substrate body is grafted with the adhesive layer through the functional groups carried by the surface with a rough structure, and the adhesive layer forms a chemical connection with the substrate background, so that the bonding force between the adhesive layer and the substrate body is greater than the bonding force between the adhesive layer and the conductive layer, and the bonding stability between the conductive layer and the substrate can be further improved. In addition, the bonding force between the adhesive layer and the substrate body is greater than the bonding force between the adhesive layer and the conductive layer, and the bonding force is reasonably distributed, which avoids the adhesive material in the adhesive layer from expanding to the conductive layer. Therefore, while improving the bonding stability between the conductive layer and the substrate body, it will not pollute the conductive layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0024] Figure 1 The present invention provides a process flow for modifying a polyacrylic acid (PAA) adhesive layer on the surface of a polyethylene terephthalate (PET) substrate body according to an embodiment.

[0025] Figure 2 These are scanning electron microscope images of the PET substrate body in Example 1 before and after the roughening treatment.

[0026] Figure 3 1 is an X-ray photoelectron spectrum of the PET substrate before and after the functional group activation treatment in step S2 of Example 1.

[0027] Figure 4 The lap shear test results of Example 1 and Comparative Examples 1-4 are shown. DETAILED DESCRIPTION

[0028] For ease of understanding of the present application, the present application will be described more fully below with reference to the relevant embodiments. The following provides preferred embodiments of the present application. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0030] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0031] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0032] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0033] The temperature parameters in this application, unless otherwise specified, allow both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0034] The selection scope of the term "and / or" used in this article includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the said any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions of "and / or", it should be understood that in this application, the technical solution undoubtedly includes technical solutions that are all connected by "logical and", and also undoubtedly includes technical solutions that are all connected by "logical or".

[0035] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.

[0036] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0037] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0038] In the description of the application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0039] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0040] Flexible electrodes are subjected to mechanical effects such as stretching, bending, and extrusion during use, and adhesion failure often occurs between layers, especially adhesion failure between the substrate and the conductive layer, which greatly affects the life and reliability of the biosensor. The inventors found that the adhesion failure between the substrate and the conductive layer is due to the weak adhesion strength between the conductive layer and the substrate in a physiological moist environment. At present, the main ways to improve the bonding force between the substrate and the conductive layer are to change the surface morphology of the substrate, such as nano- or micron-scale roughening, and chemical deposition on the surface of the substrate to generate a nano- or micron-conductive coating. The core is to increase the basic area of ​​the conductive layer and the substrate, but it is impossible to increase the interaction force between the upper layer and the layer per unit area, and the improvement of the interaction force requires the introduction of new chemical groups to further form chemical bonds or hydrogen bonds with the substrate and the conductive layer. This requires the introduction of adhesive molecules, and the existing introduction method is generally to scrape an adhesive layer on the surface of the substrate or directly mix the adhesive into the conductive layer. These two solutions are simple, but have poor stability. The adhesive molecules are easy to swell or even dissolve in a physiologically moist environment. The adhesive is easy to diffuse into the conductive layer and change the properties of the conductive layer (such as hydrophilicity and conductivity). However, this diffusion is uncontrollable and related pollution will cause unstable performance.

[0041] Based on the above problems, the present application grafts functional groups after roughening the surface of the substrate body, and grafts the adhesive through the functional groups, that is, covalently modifies the adhesive on the surface of the substrate body to form a stable adhesive layer, and the adhesive layer is chemically connected to the substrate body. Since the bonding force between the adhesive and the substrate body is greater than the bonding force between the adhesive layer and the conductive layer, a reasonable bonding force distribution is formed, and the diffusion of adhesive molecules to the conductive layer is avoided, thereby improving the bonding stability between the conductive layer and the substrate body without contaminating the conductive layer.

[0042] One or more embodiments of the present application provide a composite substrate, including a substrate body and an adhesive layer, wherein at least one side surface of the substrate body has a rough structure, the surface of the substrate body having the rough structure carries functional groups, and the adhesive layer is grafted to the substrate body through the functional groups.

[0043] It should be noted that the “rough structure” mentioned in the context refers to the uneven and uneven microstructure existing on the surface of the substrate body or within a depth range of a certain vertical distance from the surface of the substrate body.

[0044] The composite substrate of the embodiment of the present application has a rough structure on the surface of the substrate body, which can increase the area of ​​the grafted adhesive material and increase the density of the adhesive material, thereby improving the bonding stability between the conductive layer and the substrate body. At the same time, the substrate body grafts the adhesive layer through the functional groups carried by the surface with a rough structure, and the adhesive layer forms a chemical connection with the substrate background, so that the bonding force between the adhesive layer and the substrate body is greater than the bonding force between the adhesive layer and the conductive layer, which can further improve the bonding stability between the conductive layer and the substrate. In addition, the bonding force between the adhesive layer and the substrate body is greater than the bonding force between the adhesive layer and the conductive layer, and the bonding force is reasonably distributed, which prevents the adhesive material in the adhesive layer from expanding to the conductive layer. Therefore, while improving the bonding stability between the conductive layer and the substrate body, it will not contaminate the conductive layer.

[0045] It is not difficult to understand that the rough structure on the surface of the substrate body can also increase the contact area between the conductive layer and the substrate body.

[0046] In some embodiments, the specific surface area of ​​the surface of the substrate body having a rough structure is 0.01 m 2 / g-1 m 2 / g. For example, it can be, but is not limited to, 0.01 m 2 / g, 0.05 m 2 / g, 0.1 m 2 / g, 0.15 m 2 / g, 0.2 m 2 / g, 0.25 m 2 / g, 0.3 m 2 / g, 0.35 m 2 / g, 0.4 m 2 / g, 0.45 m 2 / g, 0.5 m 2 / g, 0.55 m 2 / g, 0.6 m 2 / g, 0.65 m 2 / g, 0.7m 2 / g, 0.75 m 2 / g, 0.8 m 2 / g, 0.85 m 2 / g, 0.9 m 2 / g, 0.95 m 2 / g, 1 m 2 / g or the range between any two of the above specific surface areas, etc. Thus, on the one hand, the contact area between the conductive layer and the substrate body can be increased, and on the other hand, the area where the adhesive material can be grafted can be increased, thereby increasing the density of the adhesive material and thus improving the bonding stability between the substrate body and the adhesive layer.

[0047] As a possible implementation manner, the roughness of the surface of the substrate body with the rough structure is 0.01 μm-1000 μm. For example, it can be but not limited to 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm, 800 μm, 850 μm, 900 μm, 950 μm, 1000 μm or a range between any two of the above roughnesses.

[0048] In some embodiments, the functional groups carried on the surface of the substrate body having the rough structure include one or more of hydroxyl groups, carboxyl groups, amino groups, acrylic acid groups, and acrylic acid group derivatives.

[0049] As a possible implementation, the acrylic acid group derivative includes one or more of a methacrylic acid group, a cyanoacrylic acid group and an acryloyl chloride group.

[0050] In some embodiments, in a direction perpendicular to the surface where the rough structure is located, the depth of the rough structure is 0.01 μm-1000 μm. For example, it can be, but is not limited to, 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm, 800 μm, 850 μm, 900 μm, 950 μm, 1000 μm or a range between any two of the above distances. Thus, it is beneficial to improve the roughness of the surface of the substrate body.

[0051] As a possible implementation manner, the material of the adhesive layer includes a viscous material with a molecular weight of 500Da-500000Da. As an example, the molecular weight of the viscous material can be but is not limited to 500Da, 1000Da, 5000Da, 10000Da, 20000Da, 40000Da, 60000Da, 80000Da, 100000Da, 120000Da, 140000Da, 160000Da, 180000Da, 200000Da, 220000Da, 240000Da, 260000Da, 280000Da, 300000Da, 320000Da, 340000Da, 360000Da, 380000Da, 400000Da, 420000Da, 440000Da, 460000Da, 480000Da, 500000Da or a range between any two of the above molecular weights, etc. When the molecular weight of the adhesive material is within the above range, it is beneficial to enhance the stability and adhesive force of the adhesive layer.

[0052] In some optional embodiments, the material of the adhesive layer includes one or more of polyacrylic acid, polyacrylate, cellulose, cellulose derivatives, polyvinyl alcohol, alginate, chitosan and collagen fibers.

[0053] It should be noted that polyacrylic acid and polyacrylate are chemically bonded to the functional groups grafted on the surface of the substrate body through the carboxyl groups contained in their structures, respectively. Polyvinyl alcohol is chemically bonded to the functional groups grafted on the surface of the substrate body through the hydroxyl groups contained in its structure. Alginate is chemically bonded to the functional groups grafted on the surface of the substrate body through the carboxyl groups contained in its structure. Chitosan is chemically bonded to the functional groups grafted on the surface of the substrate body through the amino groups contained in its structure. Collagen fibers are chemically bonded to the functional groups grafted on the surface of the substrate body through the amino or carboxyl groups contained in their structure.

[0054] In some exemplary embodiments, the cellulose derivative includes one or more of carboxymethyl cellulose and hydroxypropyl cellulose, wherein the carboxymethyl cellulose and hydroxypropyl cellulose are chemically bonded to the functional groups grafted onto the surface of the substrate through the carboxyl groups or hydroxyl groups contained in their structures, respectively.

[0055] In some embodiments, the alginate includes one or more of sodium alginate, potassium alginate and ammonium alginate, wherein sodium alginate, potassium alginate and ammonium alginate are chemically bonded to the functional groups grafted onto the surface of the substrate through the carboxyl groups contained in their structures.

[0056] In some embodiments, the thickness of the adhesive layer is 0.1 μm-1 μm. For example, it can be, but is not limited to, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm, 0.95 μm, 1 μm, or a range between any two of the above thicknesses. Thus, it is beneficial to increase the contact area between the adhesive layer and the substrate and the subsequent coating, while avoiding the problem of insufficient cohesion and deadweight caused by the excessive thickness of the adhesive layer, and improving the bonding stability.

[0057] As a possible implementation, in a direction perpendicular to the surface where the rough structure is located, the distance from the lowest point where the rough structure is grafted with the adhesive layer to the crest of the rough structure is 0.01 μm-200 μm; for example, it can be but not limited to 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm or the range between any two of the above distances, etc. Thus, it is beneficial to further improve the bonding stability between the conductive layer and the substrate body.

[0058] In some embodiments, the material of the substrate body includes one or more of polyethylene terephthalate, polyimide, polyethylene naphthalate, polydimethylsiloxane, polyurethane, and polycarbonate.

[0059] As a non-limiting example, the substrate body may be a modified substrate; for example, it may be a substrate modified by gold spraying, etc., and the specific details are not limited.

[0060] One or more embodiments of the present application provide a method for preparing a composite substrate, which can be used to prepare the above-mentioned composite substrate, and the method comprises the following steps:

[0061] The surface of one side of the substrate body is roughened to form a rough structure on the surface of the substrate body; the surface of the substrate body with the rough structure is activated with functional groups to graft functional groups on the surface of the substrate body with the rough structure; an adhesive material is applied to the surface of the substrate body with the rough structure to graft the functional groups with the adhesive material to form an adhesive layer on the surface of the substrate body to prepare a composite substrate.

[0062] The preparation method of the composite substrate provided in the embodiment of the present application realizes covalent modification of the adhesive on the surface of the substrate body through roughening treatment, functional group activation treatment and application of adhesive material on the surface of the substrate body with a rough structure, thereby forming a stable adhesive layer. The adhesive layer is chemically connected to the substrate body, so that the bonding force between the adhesive layer and the substrate body is greater than the bonding force between the adhesive layer and the conductive layer, forming a reasonable bonding force distribution and avoiding the adhesive material in the adhesive layer from expanding to the conductive layer. Therefore, without contaminating the conductive layer, the bonding stability between the conductive layer and the substrate body is improved.

[0063] The "roughening treatment" mentioned above refers to manufacturing a surface with greater roughness on the surface of the substrate body and within a certain depth range. In some embodiments, the method used for the roughening treatment includes one or more of mechanical grinding, sandblasting, chemical solution immersion, laser cutting and plasma treatment.

[0064] The characteristics of the rough structure obtained by the roughening treatment, the type of functional group, the type of adhesive material and the characteristics of the adhesive layer are respectively as described above and will not be repeated in the method.

[0065] In some optional embodiments, the chemical solution soaking includes acidic chemical solution soaking and alkaline chemical solution soaking.

[0066] As a possible implementation, the laser cutting includes stripe cutting.

[0067] In some of the embodiments, the plasma treatment includes plasma cleaning and deep reactive ion etching.

[0068] The "functional group activation treatment" mentioned above refers to grafting new chemical groups on the surface of the substrate body with a rough structure to make the surface of the substrate body reactive. In some embodiments, the method used for the functional group activation treatment includes one or more of chemical vapor deposition, metal sputtering, plasma treatment and solution immersion chemical grafting.

[0069] In some exemplary embodiments, the reagent used for chemical vapor deposition includes a silanization reagent of a functional group; the functional group refers to a functional group intended to be grafted on the surface of the substrate body.

[0070] In some embodiments, the metal used for metal sputtering includes one of Au, Ag and Pt.

[0071] As a possible implementation manner, the plasma used in the plasma treatment includes one of ammonia plasma and nitrogen and hydrogen mixed gas plasma.

[0072] In some optional embodiments, the reaction occurring during the solution immersion chemical grafting includes one or more of carbodiimide catalysis, Michael addition, Diels-Alder reaction, Schiff base reaction, esterification reaction and amidation reaction.

[0073] In some embodiments, the molar concentration of the functional group donor contained in the solution used for solution immersion chemical grafting is 0.01M-0.1M; for example, it can be but not limited to 0.01M, 0.02M, 0.03M, 0.04M, 0.05M, 0.06M, 0.07M, 0.08M, 0.09M, 0.1M or a range between any two of the above molar concentrations, etc.

[0074] In some embodiments, the step of applying the adhesive material to the surface of the substrate having the rough structure adopts a method comprising one or more of in-situ polymerization and solution immersion chemical grafting.

[0075] In some optional embodiments, the in-situ polymerization method includes one or more of photopolymerization, thermal polymerization and electrochemical polymerization.

[0076] In some embodiments, the reaction occurring during the solution immersion chemical grafting includes one or more of carbodiimide catalysis, Michael addition, Diels-Alder reaction, Schiff base reaction, esterification reaction, and amidation reaction.

[0077] In some optional embodiments, the mass percentage concentration of the viscous material contained in the solution used for solution immersion chemical grafting is 0.03wt%-1wt%; for example, it can be but not limited to 0.03wt%, 0.05wt%, 0.07wt%, 0.09wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt% or the range between any two of the above mass percentage concentrations, etc.

[0078] Figure 1 The process flow for modifying a polyacrylic acid (PAA) adhesive layer on the surface of a polyethylene terephthalate (PET) substrate body is provided in one embodiment; Figure 1 As shown: the surface of the PET substrate is roughened to form a rough structure on the surface of the substrate; then carboxyl groups are first grafted on the surface of the substrate with the rough structure, ethylenediamine is grafted through the carboxyl groups, and finally an adhesive material (polyacrylic acid or carboxymethyl cellulose) is grafted through the functional groups to obtain an adhesive layer.

[0079] One or more embodiments of the present application provide a flexible electrode, comprising the composite substrate or the composite substrate prepared by the above-mentioned preparation method. The bonding stability between the composite substrate and the conductive layer is effectively improved.

[0080] In some embodiments, the flexible electrode further comprises a conductive layer, an insulating layer and a sensing layer. The composite substrate, the conductive layer, the insulating layer and the sensing layer are stacked in sequence, and the conductive layer is located on the side of the composite substrate where the adhesive layer is located.

[0081] As non-limiting examples, the material of the conductive layer includes carbon-based materials, organic conductive materials and metal materials. Carbon-based materials may include but are not limited to graphene and carbon nanotubes. Organic conductive materials may include but are not limited to polyaniline and polythiophene. Metal materials may include but are not limited to silver nanowires and gold nanowires.

[0082] One or more embodiments of the present application provide a biosensor including the above-mentioned flexible electrode.

[0083] The technical scheme of the present invention is described in detail below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for which specific conditions are not specified in the following embodiments are preferably referred to the guidance given in the present invention, and can also be carried out according to the experimental manual or conventional conditions in the art, or according to the conditions recommended by the manufacturer, or with reference to experimental methods known in the art.

[0084] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.

[0085] Example 1

[0086] Step S1, using argon plasma to roughen the surface of the substrate body for 15 minutes to form a rough structure on the surface of the substrate body; wherein the material of the substrate body is polyethylene terephthalate; the power of the argon plasma is 40W and the gas pressure is 0.35mBar.

[0087] Step S2, using oxygen plasma to treat the surface of the substrate body with a rough structure for 15 minutes to graft carboxyl groups on the surface of the substrate body, wherein the power of the oxygen plasma is 40W and the air pressure is 0.35mBar. Then the treated substrate body is immersed in a 2-(N-morpholine)ethanesulfonic acid (MES) buffer with a molar concentration of 0.05M, wherein the MES buffer contains N-hydroxysuccinimide (NHS) with a molar concentration of 0.1M, 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) with a molar concentration of 0.5M and ethylenediamine (EDA) with a molar concentration of 0.01M; react on a shaker at 40°C for 24 hours to complete the functional group activation treatment, so as to continue to graft amino groups through the carboxyl groups of the substrate surface matrix. After the reaction is completed, ultrasonic cleaning is performed for 10 minutes, and repeated 3 times to remove the surface physically adsorbed molecules.

[0088] Step S3, add polyacrylic acid (PAA), N-hydroxysuccinimide (NHS) and 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) to 2-(N-morpholine)ethanesulfonic acid (MES) buffer, wherein the mass percentage concentration of PAA is 0.3wt%, the molar concentration of NHS is 0.1M, and the molar concentration of EDC is 0.5M. Place the substrate body treated in step S2 in the above solution, shake it at 40°C for 24h, and graft PAA on the surface of the substrate body with a rough structure to obtain a composite substrate. After the reaction, ultrasonic cleaning is performed for 10min, and repeated 3 times to remove the surface physically adsorbed molecules.

[0089] Example 2

[0090] The difference between the preparation method of Example 2 and the preparation method of Example 1 is that carboxymethyl cellulose is used as the viscous material to prepare the adhesive layer. The preparation process of Example 2 is as follows:

[0091] Step S1 is the same as step S1 in Example 1.

[0092] Step S2: the same as step S2 in embodiment 1.

[0093] Step S3: carboxymethyl cellulose (CMC) is used to replace polyacrylic acid (PAA), and the rest is the same as step S3 in Example 1.

[0094] Example 3

[0095] The difference between the preparation method of Example 3 and the preparation method of Example 1 is that polyvinyl alcohol is used as the viscous material to prepare the adhesive layer. The preparation process of Example 3 is as follows:

[0096] Step S1 is the same as step S1 in Example 1.

[0097] Step S2: the same as step S2 in embodiment 1.

[0098] Step S3, prepare a polyvinyl alcohol (PVA) solution with a mass percentage concentration of 0.3wt%, place the substrate body treated in step S2 in the above solution, add polyethylene glycol diglycidyl ether with a mass percentage concentration of 0.015wt%, and react on a shaking table at 40°C for 24h to graft PVA on the surface of the substrate body with a rough structure to obtain a composite substrate. After the reaction is completed, ultrasonic cleaning is performed for 10min, and repeated 3 times to remove the surface physically adsorbed molecules.

[0099] Example 4

[0100] The difference between the preparation method of Example 4 and the preparation method of Example 1 is that sodium alginate is used as the adhesive material to prepare the adhesive layer. The preparation process of Example 4 is as follows:

[0101] Step S1 is the same as step S1 in Example 1.

[0102] Step S2: the same as step S2 in embodiment 1.

[0103] Step S3, sodium alginate is used to replace polyacrylic acid (PAA), and the rest is the same as step S3 in Example 1.

[0104] Example 5

[0105] The difference between the preparation method of Example 5 and the preparation method of Example 1 is that chitosan is used as the viscous material to prepare the adhesive layer. The preparation process of Example 5 is as follows:

[0106] Step S1 is the same as step S1 in Example 1.

[0107] Step S2: the same as step S2 in embodiment 1.

[0108] Step S3: chitosan is used to replace polyvinyl alcohol (PVA), and the rest is the same as step S3 in Example 3.

[0109] Example 6

[0110] The difference between the preparation method of Example 6 and the preparation method of Example 1 is that collagen fibers are used as the viscous material to prepare the adhesive layer. The preparation process of Example 6 is as follows:

[0111] Step S1 is the same as step S1 in Example 1.

[0112] Step S2: the same as step S2 in embodiment 1.

[0113] Step S3: replacing polyvinyl alcohol (PVA) with collagen fibers, and the rest is the same as step S3 in Example 3

[0114] Example 7

[0115] The difference between the preparation method of Example 7 and the preparation method of Example 1 is that the first functional group grafted on the surface of the substrate in step S2 is changed to hydroxyl group, and polyvinyl alcohol is used as the viscous material to prepare the adhesive layer in step S3. The preparation process of Example 7 is as follows:

[0116] Step S1 is the same as step S1 in Example 1. Step S2 is to treat the surface of the substrate body with a rough structure with oxygen plasma for 5 minutes to graft hydroxyl groups on the surface of the substrate body, wherein the power of the oxygen plasma is 40W and the pressure is 0.35 mBar.

[0117] Step S3, prepare a polyvinyl alcohol (PVA) solution with a mass percentage concentration of 0.3wt%, place the substrate body treated in step S2 in the above solution, add polyethylene glycol diglycidyl ether with a mass percentage concentration of 0.015wt%, and react on a shaking table at 40°C for 24h to graft PVA on the surface of the substrate body with a rough structure to obtain a composite substrate. After the reaction is completed, ultrasonic cleaning is performed for 10min, and repeated 3 times to remove the surface physically adsorbed molecules.

[0118] Example 8

[0119] In Example 8, a polymerization reaction of acrylic acid was carried out on the surface of polyethylene terephthalate (PET) by a photochemical grafting method to complete the grafting of carboxyl groups on the surface of PET.

[0120] Step S1 is the same as step S1 in Example 1.

[0121] Step S2, using oxygen plasma to treat the surface of the substrate body with a rough structure for 5 minutes to graft hydroxyl groups on the surface of the substrate body, wherein the power of the oxygen plasma is 40W and the pressure is 0.35mBar. The substrate is immersed in an acetone solution containing a photosensitizer (phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt (LAP), 0.5%wt) for 10 minutes and dried in a light-proof environment. The treated substrate is immersed in an acrylic acid monomer solution, sealed after passing nitrogen, placed in a UV irradiation device for reaction, and then washed in a Soxhlet extractor with water as a solvent for 48 hours to remove the homopolymer.

[0122] Step S3 is the same as step S3 in Example 1.

[0123] Comparative Example 1

[0124] Step S1, using argon plasma to roughen the surface of the substrate body for 15 minutes to form a rough structure on the surface of the substrate body; wherein the material of the substrate body is polyethylene terephthalate; the power of the argon plasma is 40W and the gas pressure is 0.35mBar.

[0125] Step S2, treating the surface of the substrate body with a rough structure with oxygen plasma for 15 minutes to graft carboxyl groups on the surface of the substrate body, wherein the power of the oxygen plasma is 40 W and the gas pressure is 0.35 mBar.

[0126] Comparative Example 2

[0127] Step S1, using argon plasma to roughen the surface of the substrate body for 15 minutes to form a rough structure on the surface of the substrate body; wherein the material of the substrate body is polyethylene terephthalate; the power of the argon plasma is 40W and the gas pressure is 0.35mBar.

[0128] Step S2, using oxygen plasma to treat the surface of the substrate body with a rough structure for 15 minutes to graft carboxyl groups on the surface of the substrate body, wherein the power of the oxygen plasma is 40W and the air pressure is 0.35mBar. Then the treated substrate body is immersed in a 2-(N-morpholine)ethanesulfonic acid (MES) buffer with a molar concentration of 0.05M, wherein the MES buffer contains N-hydroxysuccinimide (NHS) with a molar concentration of 0.1M, 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) with a molar concentration of 0.5M and ethylenediamine (EDA) with a molar concentration of 0.01M; react on a shaker at 40°C for 24 hours to complete the functional group activation treatment, so as to continue to graft amino groups through the carboxyl groups of the substrate surface matrix. After the reaction is completed, ultrasonic cleaning is performed for 10 minutes, and repeated 3 times to remove the surface physically adsorbed molecules.

[0129] Comparative Example 3

[0130] The original substrate body used in Example 1 is used as Comparative Example 3.

[0131] Comparative Example 4

[0132] The PET with an adhesive layer on the surface used in the commercial continuous glucose monitoring system (CGMS) is used as comparative example 4.

[0133] It should be noted that, during the preparation of Examples 1-8 and Comparative Examples 1-2, the specific surface area, roughness, depth of the rough structure, thickness of the bonding layer, and the distance from the lowest point where the rough structure and the bonding layer are grafted to the peak of the rough structure of the surface of the obtained substrate body with a rough structure were measured, and the results are shown in Table 1.

[0134] The substrate body before and after the treatment in step S1 in Example 1 was scanned using a scanning electron microscope. The results are as follows: Figure 2 As shown. Among them, Figure 2 A in the middle is the SEM image of the PET substrate before treatment. Figure 2 Figure B is the SEM image of the PET substrate after treatment. Figure 2It can be seen that after argon treatment, dense nano-scale cracks appeared on the surface of the PET substrate.

[0135] X-ray photoelectron spectroscopy (XPS) was performed on the substrate before and after the functional group activation treatment in step S2 of Example 1. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that after the functional group activation treatment in step S2, the nitrogen content of the PET substrate body is significantly increased, indicating that the amino group is successfully grafted onto the surface of the PET substrate body.

[0136] The adhesion strength between the substrate body and the conductive carbon layer of the above-mentioned embodiments and comparative examples in dry and wet states was tested by lap shear test. The test results of the above-mentioned embodiments and comparative examples are shown in Table 1. Figure 4 As shown. Among them, Figure 4 MylarA-PAA represents the PET composite substrate prepared in Example 1; MylarA-Ar+O represents the PET substrate body after argon plasma roughening and oxygen plasma grafting of carboxyl groups in Comparative Example 1; MylarA-EDA represents the amino-modified PET substrate body after ethylenediamine modification in Comparative Example 2; MylarA represents the original PET substrate body in Comparative Example 3; CGMS represents the commercial PET substrate body with an adhesive layer on the surface.

[0137] Table 1

[0138]

[0139] The specific surface area in Table 1 refers to the specific surface area of ​​the surface of the substrate body with the rough structure; the distance refers to the distance from the lowest point where the rough structure is grafted with the adhesive layer to the peak of the rough structure. "NA" means not applicable.

[0140] From the comparison of the results of Examples 1-8 and Comparative Examples 1-4 in Table 1, it can be seen that the composite substrate provided by the present application has excellent bonding stability with the conductive layer in both dry and wet states.

[0141] From Table 1 and Figure 1It can be seen that in the dry state, the Ar+O plasma treatment in Comparative Example 1 significantly improved the bonding force between the substrate and the conductive carbon layer, the grafting of EDA in Comparative Example 2 did not further improve the bonding force, and the MylarA-PAA composite substrate to which the adhesive PAA was further grafted in Example 1 had the strongest bonding force between the conductive carbon layer, which was significantly higher than the commercial CGMS with an adhesive layer in Comparative Example 4. In the wet state, the bonding force between the commercial CGMS with an adhesive layer in Comparative Example 4 and the original PET substrate MylarA in Comparative Example 3 and the conductive carbon layer was significantly reduced, but the Ar+O plasma treatment in Comparative Example 1 significantly improved the wet bonding force between the substrate and the conductive carbon layer, and the reduction was not obvious compared with the dry state, the grafting of EDA in Comparative Example 2 did not further improve the bonding force, and the MylarA-PAA composite substrate to which the adhesive PAA was further grafted in Example 1 had the strongest wet bonding force between the conductive carbon layer. Therefore, the chemical grafting of the adhesive layer on the PET substrate body can significantly improve the bonding force between the substrate and the conductive carbon layer in the dry and wet states, and can significantly avoid the decrease in bonding force in the wet state, and is expected to be used to prepare sensor devices with longer life and more stable performance.

[0142] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0143] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims, and the specification and drawings may be used to interpret the scope of the claims.

Claims

1. A composite substrate, characterized in that: include: A substrate body, wherein at least one side of the surface of the substrate body has a rough structure, and the surface of the substrate body having the rough structure carries functional groups; and The adhesive layer is grafted onto the substrate body through the functional group.

2. The composite substrate according to claim 1, characterized in that The specific surface area of ​​the surface of the substrate body having the rough structure is 0.01 m 2 / g-1 m 2 / g; and / or The roughness of the surface of the substrate body having the rough structure is 0.01 μm-1000 μm.

3. The composite substrate according to claim 1, characterized in that The functional group includes one or more of a hydroxyl group, a carboxyl group, an amino group, an acrylic acid group and an acrylic acid group derivative; Optionally, the acrylic acid group derivative includes one or more of a methacrylic acid group, a cyanoacrylic acid group and an acryloyl chloride group.

4. The composite substrate according to claim 1, characterized in that In a direction perpendicular to the surface where the rough structure is located, the depth of the rough structure is 0.01 μm-1000 μm.

5. The composite substrate according to claim 1, wherein The material of the adhesive layer includes a viscous material with a molecular weight of 500Da-500000Da; Optionally, the material of the adhesive layer includes one or more of polyacrylic acid, polyacrylate, cellulose, cellulose derivatives, polyvinyl alcohol, alginate, chitosan and collagen fibers; Optionally, the cellulose derivative includes one or more of carboxymethyl cellulose and hydroxypropyl cellulose; Optionally, the alginate includes one or more of sodium alginate, potassium alginate and ammonium alginate.

6. The composite substrate according to claim 1, wherein The thickness of the adhesive layer is 0.1 μm-1 μm; and / or In a direction perpendicular to the surface where the rough structure is located, the distance from the lowest point where the rough structure is grafted with the adhesive layer to the crest of the rough structure is 0.01 μm-200 μm.

7. The composite substrate according to any one of claims 1 to 6, characterized in that The material of the substrate body includes one or more of polyethylene terephthalate, polyimide, polyethylene naphthalate, polydimethylsiloxane, polyurethane and polycarbonate.

8. A flexible electrode, characterized in that: Comprising the composite substrate according to any one of claims 1 to 7.

9. The flexible electrode according to claim 8, characterized in that: The flexible electrode further comprises a conductive layer, an insulating layer and a sensing layer. The composite substrate, the conductive layer, the insulating layer and the sensing layer are stacked in sequence. The conductive layer is located on the side of the composite substrate where the adhesive layer is located.

10. A biosensor, characterized in that: Comprising the flexible electrode as described in any one of claims 8 to 9.